2016
DOI: 10.1016/j.yhbeh.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The BB2 receptor antagonist BW2258U89 attenuates the feeding responses evoked by exogenous gastrin releasing peptide-29

Abstract: This confirmatory work is aimed to test that the hypothesis that the gastrin releasing peptide (GRP) receptor – the BB2 receptor – is necessary for reduction of meal size (MS) and prolongation of the intermeal interval (IMI) by the small and the large forms of GRP in the rat, GRP-10 and GRP-29, and to confirm the sites of action regulating such responses – the vascular bed of the celiac artery (CA, supplying stomach and upper duodenum). To pursue these aims we measured first MS and IMI length in response to GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The catheterization procedures have been described in detail in our recent work (Sayegh et al, 2015; Washington et al, 2014; Washington et al, 2016a; Washington et al, 2016b; Williams et al, 2016). All catheters (Micro-Renathane Braintree Scientific R-ITC-SP 9.5) were 9.5" in length.…”
Section: Methodsmentioning
confidence: 99%
“…The catheterization procedures have been described in detail in our recent work (Sayegh et al, 2015; Washington et al, 2014; Washington et al, 2016a; Washington et al, 2016b; Williams et al, 2016). All catheters (Micro-Renathane Braintree Scientific R-ITC-SP 9.5) were 9.5" in length.…”
Section: Methodsmentioning
confidence: 99%
“…One catheter was implanted in each rat, as described previously (13, 14, 2022). Catheters (Micro-Renathane R-ITC-SP 9.5, Braintree Scientific, Braintree MA) were 24 cm long.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that GRP alters the previous feeding behaviors, i.e. MS, IMI and SR, (712) through sites supplied by the celiac artery (CA, supplies stomach and upper duodenum) (13, 14). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations